The Volume of Trade in Differentiated Intermediate Goods: Theory and Evidence - Harrigan, James (The Review of Economics and Statistics, 1995)
This paper develops a model of trade in differentiated intermediate goods and shows how the structure of the importing country's production will influence gross bilateral import volumes. A regression equation directly implied by the model is estimated using disaggregated bilateral trade data for the OECD countries in 1985. The data reject the model. A more general model suggested by the theory establishes strong links between a country's factor endowments and its gross trade volume. This model is dominated statistically by a fixed effects model and does not substantially alter the conclusions of earlier empirical studies about openness to trade in manufactured goods. Copyright 1995 by MIT Press.